ILMU TAJWID DAN IMPLIKASINYA TERHADAP ILMU QIRA’AH - Ahmad Hanifuddin Ishaq; Ruston Nawawi (QOF, 2017)
The fundamental thing that is rarely touched by the academics today is the science of tajwid, whereas functionally science of tajwid is a component of science which is the basis for how to read the Qur’an properly and correctly. It is a measure for every letter which is pronounced by qari ‘(reader), because in every letter of the verses of the Qur’an has its right. Another important thing to note is that the science of tajwid is not born of a vacuum, it is formed from various historical entities that surround it, and therefore tracing the historical roots of this study is a necessity. From historical aspect will be found the roots of the science of tajwid formation is inseparable from the development of science qira’ah. This is because qiraah scholars in their masterpiece also attach a lot of rules about science of tajwid. Departing from it, it can be said science of tajwid discipline has given birth to the implications of the development of science qiraah. Nevertheless, the two brothers of this disciplinary scholarship have substantial substantial differences. The science of qiraah discusses the variety of reading articulately, while the science of tajwid discusses the technicalities of the Qur’anic verses.